2013
DOI: 10.1007/s10464-013-9596-0
|View full text |Cite
|
Sign up to set email alerts
|

Conjoint Community Resiliency Assessment Measure‐28/10 Items (CCRAM28 and CCRAM10): A Self‐report Tool for Assessing Community Resilience

Abstract: Community resilience is used to describe a community's ability to deal with crises or disruptions. The Conjoint Community Resiliency Assessment Measure (CCRAM) was developed in order to attain an integrated, multidimensional instrument for the measurement of community resiliency. The tool was developed using an inductive, exploratory, sequential mixed methods design. The objective of the present study was to portray and evaluate the CCRAM's psychometric features. A large community sample (N = 1,052) were asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
139
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(162 citation statements)
references
References 41 publications
7
139
2
3
Order By: Relevance
“…The survey contained 37 fixed statements adapted from validated versions of Likert scales presented in the literature related to the community resilience capacities being studied (Lewicka 2008, Pfefferbaum et al 2011, Leykin et al 2013. Respondents were asked to rate how strongly they agreed with each statement using a five-point Likert scale (1 = strongly disagree, 2 = disagree, 3 = neither disagree or agree, 4 = agree, 5 = strongly agree).…”
Section: Methodsmentioning
confidence: 99%
“…The survey contained 37 fixed statements adapted from validated versions of Likert scales presented in the literature related to the community resilience capacities being studied (Lewicka 2008, Pfefferbaum et al 2011, Leykin et al 2013. Respondents were asked to rate how strongly they agreed with each statement using a five-point Likert scale (1 = strongly disagree, 2 = disagree, 3 = neither disagree or agree, 4 = agree, 5 = strongly agree).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have highlighted that place attachment is a key factor of community resilience [54]. Leykin et al believe that place attachment is a key construct in measuring community resilience [55]. Maclean et al note that the people-place connection is one of six attributes of community resilience [56].…”
Section: Place Attachmentmentioning
confidence: 99%
“…In this model, community resilience is composed of the social and economic well-being of a community, physical and psychological health of a population, effective risk communication, social connection and integration, and involvement of both governmental and non-governmental organizations (NGOs). Prior empirical research, such as the study of Leykin et al [30] in Israel and the investigation of Pfefferbaum et al [31] in an impoverished urban community in the United States revealed that the number of years living in a community, engagement with or volunteering in local entities/activities for DRR, having permanent relationships, and home ownership were positively correlated with perceived community resilience, whereas gender, home emergency preparedness, total family income, employment status, past emergency situations, and level of education had no statistically significant impact. In another study with affiliated volunteer responders in an American community, Pfefferbaum and colleagues [32] indicated that the completion of a basic training program in disaster response and the interest in deploying such a program within a community was negatively associated with the responders’ perception of community resilience.…”
Section: Introductionmentioning
confidence: 99%